2021
DOI: 10.1002/anie.202103805
|View full text |Cite
|
Sign up to set email alerts
|

Development of Continuous Flow Systems to Access Secondary Amines Through Previously Incompatible Biocatalytic Cascades**

Abstract: A key aim of biocatalysis is to mimic the ability of eukaryotic cells to carry out multistep cascades in a controlled and selective way. As biocatalytic cascades get more complex, reactions become unattainable under typical batch conditions. Here a number of continuous flow systems were used to overcome batch incompatibility, thus allowing for successful biocatalytic cascades. As proof‐of‐principle, reactive carbonyl intermediates were generated in situ using alcohol oxidases, then passed directly to a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 47 publications
(86 reference statements)
1
43
0
Order By: Relevance
“…The AcCO6 mutant had higher thermotolerance and better conversion in organic solvents than the wild-type AcCO. Multistep synthesis using AcCO6 has been reported in a sequential amination cascade with aminating enzymes, in both batch [ 33 ] and more recently in continuous flow using a specially designed flow reactor for the enhancement of oxygen-dependent biocatalysts [ 5 , 34 ]. Recently, AcCO6 has also been studied as a catalyst within an in vivo system for the first time [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AcCO6 mutant had higher thermotolerance and better conversion in organic solvents than the wild-type AcCO. Multistep synthesis using AcCO6 has been reported in a sequential amination cascade with aminating enzymes, in both batch [ 33 ] and more recently in continuous flow using a specially designed flow reactor for the enhancement of oxygen-dependent biocatalysts [ 5 , 34 ]. Recently, AcCO6 has also been studied as a catalyst within an in vivo system for the first time [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was overcome with the AcCO6 variant as the oxidation was irreversible. This cascade was also transferred into continuous flow, with a flow reactor that supplied above ambient in situ soluble oxygen, which enhanced the rate of the enzyme [ 34 ]. For example, the batch reaction was limited to 25 mM substrate concentration and took 24 h to go to completion on a preparative scale.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a relatively new area of study, it has become very popular in recent years [72] . Examples on the application of continuous flow setups in multistep enzymatic cascades have led to higher productivities and easier downstream processes, and have demonstrated that previously incompatible cascades can now be run efficiently [73] . We clearly believe that the combination of continuous flow systems and chemoenzymatic cascades will lead to a greater uptake and use of these multistep processes at scale.…”
Section: Discussionmentioning
confidence: 99%
“…Mattey and co-workers have investigated continuous flow systems in an effort to separate otherwise incompatible systems, and applied these to reductive amination cascade reactions. 77 A multipoint injection reactor (MPIR) was employed in which an immobilised choline oxidase mutant first generated aromatic aldehydes from alcohol substrates. The product was then fed into a reactor containing the immobilised RedAm from Ajellomyces dermatitidis (AdRedAm) and a glucose dehydrogenase for NADPH recycling.…”
Section: Applications In Cascadesmentioning
confidence: 99%